Pharmacological and pathological modulation of cerebral physiology. Issue 12 (December 2016) - Hirsch, Nicholas; Taylor, Christopher
Abstract: Anaesthesia for neurosurgery aims to provide optimal surgical conditions whilst maintaining adequate cerebral blood flow in order to supply the brain with appropriate amounts of oxygen and glucose. Most anaesthetic drugs influence the normal cerebral physiology either directly or indirectly. They can cause changes in cerebral blood flow by influencing cerebral blood vessel calibre, by interfering with autoregulatory processes and by modifying cerebral metabolism. The brain's limited ability to store oxygen and glucose means that its supply must be continuous if neuronal damage is to be avoided. Ischaemic cerebral damage is the most important pathological mechanism in patients with stroke, subarachnoid haemorrhage and traumatic brain injury. Significant traumatic brain injury causes widespread derangement of cerebral physiology, including changes in cerebral blood flow, autoregulation and cerebral energy dynamics. This article outlines the effect of anaesthesia on cerebral physiology and reviews the pathophysiology of traumatic brain injury and subarachnoid haemorrhage.